“We have a lot of battles to fight”: The experiences of older, Black, same-gender-loving women during the COVID-19 pandemic - Robynn Ashenden; Porsha Hall; Mary Anne Adams; Dipa Sharma Gautam; Jennifer Horn; Tonia Poteat (Social Sciences and Humanities Open)
Previous studies show mental and physical health inequities have been exacerbated by the COVID-19 pandemic, but few use an intersectional lens to identify the assets and unmet needs of groups that are multiply marginalized by their social categories. This study explores how older, Black, same-gender-loving women discussed their experiences during the COVID-19 pandemic with a focus on health. Sixteen focus groups were conducted between July and December 2020 with 4–8 participants each (N = 102) from across the U.S. Content analysis revealed insight into the determinants of health among older, Black, same-gender-loving women, impacts of the pandemic, and how participants were able to maintain their health. Participants’ experiences with healthcare were most prominently shaped by their intersectional social categories, as they faced complex systems of oppression rooted in heterosexism, racism, sexism, and ageism. We found discrimination to be the most prominent determinant of health, manifesting through various barriers and a lack of access to providers of preferred social categories. The complex trauma experienced during the Trump Administration, COVID-19 lockdowns, and racial unrest after the murder of George Floyd had generally negative impacts on daily life, relationships, and mental health. However, these were mitigated for some through positive internal and external coping strategies, including online resource use, mutual aid, and telehealth experiences. As evidenced by these experiences, future research and interventions need to adopt an intersectional lens and center multiply marginalized groups to mitigate future harms and promote health equity.